2006
DOI: 10.1506/7h81-8j8x-c6rt-uvjp
|View full text |Cite
|
Sign up to set email alerts
|

How Has Regulation FD Affected the Operations of Financial Analysts?*

Abstract: In this paper, we analyze how financial analysts generate information, make decisions about firm coverage, and try to maintain their forecasting accuracy after the passage of Regulation Fair Disclosure ("Reg FD"). Using the model developed by Barron, Kim, Lim, and Stevens 1998, we find that analysts are investing more effort in idiosyncratic information discovery. In order to do this, individual analysts appear to be reducing coverage for well-followed firms while increasing coverage of firms that were less fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
135
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(151 citation statements)
references
References 20 publications
15
135
0
1
Order By: Relevance
“…The 12 large investment banks involved in this agreement are compelled to clearly separate their financial research and investment banking activities. A great deal of empirical literature shows that the GS was effective in reducing analysts' optimistic bias (Heflin et al, 2003, Mohanram and Sunder, 2006, Kadan et al, 2009, Clarke et al, 2011, Guan et al, 2012, Hovakimian and Saenyasiri, 2010, 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 12 large investment banks involved in this agreement are compelled to clearly separate their financial research and investment banking activities. A great deal of empirical literature shows that the GS was effective in reducing analysts' optimistic bias (Heflin et al, 2003, Mohanram and Sunder, 2006, Kadan et al, 2009, Clarke et al, 2011, Guan et al, 2012, Hovakimian and Saenyasiri, 2010, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…By prohibiting any form of selective information release by large firms to analysts or investors, the Regulation Fair Disclosure Act, which was implemented in the US in October 2000, is intended to curb such behavior (Heflin et al, 2003, Mohanram andSunder, 2006). and investment banking, the aim of the rules governing CSAs is to eliminate conflicts of interest between financial research and brokerage activities.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, studies have shown that analysts' forecasts have become less precise (Gintschel and Markov, 2004;Agrawal, Chadha, and Chen, 2006), analysts' forecast dispersion has increased (Bailey et al, 2003;Mohanram and Sunder, 2006), and analyst coverage has declined (Mohanram and Sunder, 2006). The results collectively suggest that private communications with managers were an important input for analysts in their production of information.…”
Section: Role Of Regulationmentioning
confidence: 94%
“…Furthermore, the SEC has also approved the use of social media for company announcements (www.sec.gov/News/PressRelease/Detail/PressRelease/1365171513574). There is significant literature that discusses how the availability of online information has reduced information asymmetry between management and shareholders, where management includes the board (Brown and Hillegeist, 2007;Brown et al, 2004;Fu et al, 2012;Healy and Palepu, 2001;Merton, 1987;Mohanram and Sunder, 2006;Nasri, 2013;Van Buskirk, 2012). In our model, the informedness parameter…”
Section: Model Of Delegated Governance and Board Entrenchmentmentioning
confidence: 99%